Brief Report: Obesogenic Behaviors of Children with Developmental Disabilities During Summer. - Brazendale, Keith; Brazendale, Allison B.; Garcia, Jeanette M.; Monroe, Courtney M.; Weaver, R. Glenn; Beets, Michael W. (Journal of Autism & Developmental Disorders, 2021)
The 'Structured Days Hypothesis' suggests that children's obesogenic behaviors (e.g., activity, diet, sleep, and screen time) are less favorable during times when there is less-structure to a child's day (e.g., summer). To compare obesogenic behaviors of children with developmental disabilities (DD) during summer on days with differing amounts of 'structure'. Seventeen children with DD (mean age 9.8 years) attending a day camp wore a Fitbit© activity monitor on the non-dominant wrist during summer, and parents completed a survey packet, to capture obesogenic behaviors. Participants displayed improved physical activity levels, diets, and sleep timing on camp days versus other days. Providing children with DD 'structure' over summer is a potential intervention approach requiring further investigation.